INTERPRETASI STRUKTUR BAWAH PERMUKAAN DAERAH MANIFESTASI MINERAL EMAS SISTEM EPITHERMAL DENGAN METODE POLARISASI TERIMBAS (INDUCED POLARIZATION) DI DAERAH “X” KABUPATEN GARUT JAWA BARAT - Alifa Rusyda; Tony Yulianto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
A geophysical investigation has been done using Induced Polarization Method at area “X”, Garut, West Java. The purpose of this investigation is to identify the sub-surface stucture of a minerals gold epithermal system manifestation area.The research area is a gold prospect area which is a mining concession area ofAneka Tambang, Tbk. Stratigraphy lithology constituent part of the study area Jampang Formation which consists of andesite lava, andesite breccia, hornblende, and fine tuffaceous rocks. Induced Polarization method is usingelectrical properties of rocks by detecting the electrical polarization on the surface of metallic minerals beneath the earth's surfaceThe processed data is measured with Dipole-dipole configuration, with electrodes spaced 25 meters. Path length 200 meters, so the expected penetration depth reaches 600 meters. Data processing use software AGI EarthImager2D and Geosoft , is obtain imaging the model 2D and 3D subsurface. The processing results is present in 2D and 3D, From the modeling results indicate that the tuff and Crystallin Tuff rock and minerals sulphide (si-ka-il, ka-il) with resistivity values ranging from 150 to more than 1000 ohm.m ohm.m and chargeabilitas values ranged from 100 ms to more than 300 ms, distribution pattern is decreased from north to south and then to east in penetration depth reaches 600 meters of subsurface.Volume for estimated potential of minerals gold epithermal system manifestation is 161.302.421,7 m3Keywords: Gold, Epithermal System, Induced Polarization, AGI EarthImager2D, Geosoft